Nutrient and manganese pollution in groundwater of the northeastern Nile Delta: distribution, sources, and health risks - Mohammed Hagage; Abdel Galil A. Hewaidy; Abdulaziz M. Abdulaziz; Said A. Shetaia (Applied Water Science)
Abstract Groundwater pollution poses significant health and environmental risks, particularly in regions heavily reliant on this resource. This study assessed nutrient and manganese pollution in groundwater of the northeastern Nile Delta, identifying pollution sources and evaluating associated health risks. An integrated methodology was employed, incorporating water pollution indices, health risk modeling, satellite imagery analysis, and statistical analysis. Thirty-one groundwater samples were analyzed for nitrate, nitrite, ammonia, phosphate, and manganese. Concentrations ranged from 0.3 to 52 mg/L, 0.2 to 11.3 mg/L, 0.02 to 25 mg/L, 0.1 to 2.3 mg/L, and 0.01 to 1.94 mg/L, respectively. The nitrate pollution index (NI) classified 80.6% of samples as polluted to varying degrees, while the nutrient pollution index (NPI) indicated that 67.7% were moderately to highly polluted. The heavy metal toxicity load for Mn (MTL) suggested that 61.3% of samples surpassed the manganese toxic load of 239.4 mg/L, and groundwater in the western regions needs treatment to remove over 60% of manganese to mitigate potential health risks. The correlation coefficient analysis revealed strong correlations between satellite-derived land-use and pollutant concentrations. It showed a strong positive correlation between agricultural areas derived from the Normalized Difference Vegetation Index (NDVI) and ammonia and manganese levels, and a strong positive correlation between urban areas derived from the Normalized Difference Built-up Index (NDBI) and nitrate concentrations. Moreover, surface irrigation water displayed severe nutrient pollution, highlighting its role as a major pollution source alongside land use. The total health risk (HItotal) for nitrates and manganese ranged from 0.016 to 1.07 and 0.04 to 1.633, respectively, with 9.6% and 16.1% of samples indicating non-carcinogenic risk (HItotal > 1) for adults and children, respectively. This comprehensive study provides crucial insights for groundwater management in the region, identifying areas requiring urgent mitigation measures to protect public health and ensure sustainable water resource management.